Characterization of Congregicoccus parvus gen. nov., sp. nov., a novel slow-growing ultramicrobacterium of the phylum Verrucomicrobiota - Md. Samiul Islam; Kyosuke Yamamoto; Naoki Morita; Wataru Kitagawa; Isao Yumoto; Souichiro Kato; Ryosuke Nakai; Kensuke Igarashi (PLoS ONE, 2025)
The bacterial phylum Verrucomicrobiota is a typical representative of challenging-to-culture lineages. Here, we isolated a novel slow-growing Verrucomicrobiota bacterium, designated ASA1T, from garden soil. Phylogenetic analyses suggested that strain ASA1T was affiliated with a novel candidate in the family Alterococcaceae of the class Opitutia (previously Opitutae), exhibiting low 16S rRNA gene sequence identities (<93%) and average nucleotide identity values (<77%) to the closest type strain. Furthermore, average amino acid identity analysis (AAI) showed that ASA1T shares <54% AAI identity with Opitutia representatives, well below the 60–65% genus threshold, supporting its classification as a novel genus. In addition to its genomic characteristics, ASA1T exhibits distinctive morphological features, including an ultramicrobacterial cell size (0.05–0.07 μm3) and cluster-like aggregation (>10 µm). Strain was Gram-negative, aerobic, and motile, with menaquinone-7 as its primary respiratory quinone and a fatty acid profile dominated by anteiso-C15:0 (53%) and C16:0 (15%). Based on these results, we propose that strain ASA1T represents a novel genus and species named Congregicoccus parvus gen. nov., sp. nov. (JCM 36569T = NCIMB 15508T) of the Alterococcaceae family. Habitability analysis suggested that ASA1T relatives were distributed in the soil and other environments, such as freshwater and activated sludge. Additional genome analysis of strain ASA1T revealed six unique biosynthetic gene clusters with no related clusters identified via antiSMASH, suggesting a potential source of novel bioactive compounds for future research.